1993
DOI: 10.1111/j.1472-765x.1993.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of selected food-borne bacteria by tannic acid, propyl gallate and related compounds

Abstract: Tannic acid, propyl gallate, gallic acid and ellagic acid were tested for their inhibitory effects on selected food‐borne bacteria by the well assay technique. Tannic acid and propyl gallate were inhibitory whereas gallic acid and ellagic acid were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 8 publications
6
82
0
2
Order By: Relevance
“…All plants used in the traditional medicine mostly have moderate antimicrobial activities as reported earlier (Rehab, 2015;Rehab, 2017;Chung et al,1993;Chung et al, 1998;Sasikumar et al, 2005;Alkhazaragi, 1991).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…All plants used in the traditional medicine mostly have moderate antimicrobial activities as reported earlier (Rehab, 2015;Rehab, 2017;Chung et al,1993;Chung et al, 1998;Sasikumar et al, 2005;Alkhazaragi, 1991).…”
Section: Resultsmentioning
confidence: 85%
“…Phytochemical constituents such as tannins, saponins, flavonoids, alkaloids, and several other aromatic compounds are secondary metabolites of plants that serve as defense mechanisms against predation by many microorganisms, insects, and other herbivores. (Rehab, 2017;Chung et al, 1993).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Besides, Chung et al [12] reported that tannic acid inhibited the growth of all selected food-borne bacteria while gallic and ellagic acid could not inhibit any of them. Chung et al [12] and [13] reported that the ester linkage between gallic acid and glucose (to form tannic acid) was important for the antimicrobial potential of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids and flavonoids act as an effective antimicrobial agent due to its ability to disrupt the membrane of lipophilic compounds present in the microbial cell [52]. The antibacterial ability of the extract may also be due to the ability of tannin to hydrolyze the ester linkage between gallic acid and polyols [53]. Thus, tannin-rich plant parts have natural defense against microbial infection [54].…”
Section: Antibacterial Activitymentioning
confidence: 99%